PERI-CARE : Pemberdayaan Ibu Hamil Trimester III Melalui Edukasi Dan Pelatihan Pijat Perineum Untuk Mencegah Ruptur Perineum - Bima Suryantara; Mia Dwi Agustina; Riyantika Riyantika (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Perineal rupture is one of the most common complications of vaginal delivery and may lead to pain, bleeding, infection, and decreased quality of life during the postpartum period. Limited knowledge among pregnant women regarding the prevention of perineal rupture highlights the need for appropriate education and training. This community service program aimed to improve the knowledge and skills of third-trimester pregnant women through education and perineal massage training as an effort to prevent perineal rupture. The PERI CARE program was conducted in the working area of Dukuhseti Public Health Center, Pati Regency, involving 25 third-trimester pregnant women. The methods included health education sessions, demonstrations of perineal massage techniques using anatomical models, hands-on practice (re-demonstration), and evaluation through pre-test and post-test assessments. The results showed an increase in participants’ knowledge, with the mean pre-test score increasing from 62.4 to 87.6 in the post-test. The proportion of participants with good knowledge increased from 20% to 88%, while those with poor knowledge decreased from 32% to 0%. Furthermore, 88% of participants were able to independently perform the perineal massage technique according to the recommended procedure. The findings indicate that education and training on perineal massage are effective in improving the knowledge and skills of third-trimester pregnant women. The PERI CARE program can serve as a promotive and preventive